Comprehensive evaluation of the resistance to shoot shriveling before and after sprouting in different varieties of Ping’ou hybrid hazelnut - Gao, Haizhe; Jia, Zhiguo; Zhang, Lirong; Li, Zhang (Frontiers in Forests and Global Change, 2024)
Introduction The hybrid hazelnut is an important fruit tree species known for its high productivity and disease resistance. However, during the growth process of hybrid hazelnuts, issues such as branch withering and bud wrinkling have attracted significant attention. These phenomena severely impact the normal development and yield of the plants. This study aimed to investigate the relationship between the resistance to shoot emergence and physiological changes in six hazel tree varieties by comprehensively analyzing their resistance to shoot emergence. Method Six widely cultivated hazelnut hybrid varieties were selected for physiological measurements and field surveys using one-year-old branches and buds as test materials. The resistance to shoot emergence of different hazel tree varieties was evaluated through correlation analysis, principal component analysis, and membership function evaluation. Results The results showed that the length and width of hazel buds gradually increased while the thickness first increased and then decreased before and after bud burst. The carbohydrate levels of the ‘Dawei’, ‘Pingou 110’, and ‘84–237’ varieties were significantly higher than those of other varieties. The content of reducing sugars and starch in hazel buds generally increased and then decreased during the bud burst process, while α-amylase activity showed a decreasing trend followed by an increasing trend. The antioxidative enzyme activity of ‘Dawei’ was significantly higher than that of other varieties on different sampling dates. The soluble protein content, POD enzyme activity, and CAT enzyme activity of hazel buds for the six varieties gradually decreased. The moisture content of ‘Pingou 210’ shoots was significantly higher than that of other varieties during the peak emergence period. The correlation analysis results showed that the bud burst rate of hazel trees was positively correlated with the length, width, thickness, reducing sugar content, starch content, POD enzyme activity, CAT enzyme activity, and shoot moisture content, while it was negatively correlated with α-amylase activity and relative conductivity of shoots. Through a comprehensive evaluation using correlation analysis, principal component analysis, and membership function analysis, the resistance to shoot emergence of the six hazel tree varieties was ranked in the following order: ‘Dawei’, ‘Pingou 110’, ‘84–237’, ‘Pingou 210’, ‘Yuzhui’, and ‘Liaozhen 3’. Discussion This study fills a research gap regarding the physiological changes of hazelnuts before and after sprouting, and provides theoretical guidance for further research on the anti-withering ability of hazelnut trees.